Tuning of Polyoxopalladate Macroanionic Hydration Shell via Countercation Interaction. Issue 12 (29th January 2018) - He, Jiazhi; Li, Hui; Yang, Peng; Haso, Fadi; Wu, Jiayingzi; Li, Tao; Kortz, Ulrich; Liu, Tianbo
Abstract: Three types of macroanion–countercation interactions in dilute solution, decided by the strength of electrostatic attraction and the change of hydration shells are reported: minor interaction between macroanions [MO8 Pd12 (SeO3 )8 ] 6− (M=Zn 2+ or Ni 2+ ) and monovalent cations (Na +, K +, Rb +, Cs + ), leaving their hydration shells intact (solvent‐separated ion‐pairs); strong binding between macroanions and divalent cations (Sr 2+, Ba 2+ ) to form solvent‐shared ion‐pairs with partial dehydration; very strong electrostatic attraction between macroanions and Y 3+ ion with contact ion‐pairs formation by severely breaking their original hydration shells and forming new ones. In addition, divalent cations can help the macroanions self‐assemble into hollow spherical blackberry structures through counterion‐mediated attraction, whereas macroanions with mono‐ or trivalent cations only stay as discrete ions due to either weak interaction or a small number of bound countercations. Abstract : Mix and interact : Three types of polyoxopalladate macroanion–countercation interactions in dilute solution, decided by the strength of electrostatic attraction and the change of hydration shells are reported. The different polyoxopalladate macroanion‐countercation pairs and the corresponding alternation of their hydration shells are depicted (from left to right, solvent‐separated, solvent‐shared, and contact ion‐pair).